2016
DOI: 10.3892/ol.2016.4560
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of secreted frizzled-related protein 2 and nuclear accumulation of β-catenin in aggressive nonfunctioning pituitary adenoma

Abstract: Abstract. The identification of a specific molecular marker for aggressiveness of nonfunctioning pituitary adenomas (NFPAs) is urgently required in order to guide the clinical diagnosis and treatment of NFPAs. In the present study, low expression of secreted frizzled-related protein 2 (sFRP2) in NFPAs was demonstrated by reverse transcription-quantitative polymerase chain reaction, western blot and immunohistochemical analyses. The results confirmed an abnormal accumulation of free β-catenin in the nuclei of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In this study, PTMScan experiment found the increased level of Bcl9 in NFPAs, and upregulations of many target genes such as c-Myc and c-Jun in canonical Wnt pathway. Moreover, some studies clearly demonstrated that β-catenin was accumulated in the nucleus of NFPAs (22), several Wnt target genes such as Cyclin D1 and c-MY were upregulated in NFPAs (21,22), and the inhibitor of Wnt pathway including Wnt inhibitory factor 1 (WIF1) and secreted frizzled related protein (sFRP) were significantly decreased in NFPAs (22,46). All these data revealed that canonical Wnt pathway was activated in NFPAs to participate in cell apoptosis, proliferation, differentiation, and motility.…”
Section: Canonical Wnt Pathway Was Activated In Nfpasmentioning
confidence: 99%
“…In this study, PTMScan experiment found the increased level of Bcl9 in NFPAs, and upregulations of many target genes such as c-Myc and c-Jun in canonical Wnt pathway. Moreover, some studies clearly demonstrated that β-catenin was accumulated in the nucleus of NFPAs (22), several Wnt target genes such as Cyclin D1 and c-MY were upregulated in NFPAs (21,22), and the inhibitor of Wnt pathway including Wnt inhibitory factor 1 (WIF1) and secreted frizzled related protein (sFRP) were significantly decreased in NFPAs (22,46). All these data revealed that canonical Wnt pathway was activated in NFPAs to participate in cell apoptosis, proliferation, differentiation, and motility.…”
Section: Canonical Wnt Pathway Was Activated In Nfpasmentioning
confidence: 99%
“…Thus, SFRP2 may be a useful marker for predicting characteristics of pituitary ACTH adenoma. In fact, researchers have already reported that SFRP2 expression is associated with the degree of tumor malignancy and invasive ability in various human cancers ( 12 , 18 ). However, this is the first description of the aberrant expression of SFRP2 in the tumorigenesis of CD.…”
Section: Discussionmentioning
confidence: 99%
“…The 5 µ m thick sections were prepared from the formalin-fixed and paraffin embedded tissues (3 NHP and 23 CD). IHC staining was performed as previously reported ( 12 ). Specific primary antibody against SFRP2 (dilution 1:200; cat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations